2007
DOI: 10.1111/j.1600-6143.2007.01928.x
|View full text |Cite
|
Sign up to set email alerts
|

Renin Angiotensin System Blockade in Kidney Transplantation: A Systematic Review of the Evidence

Abstract: ACE-inhibitors and angiotensin receptor blockers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
4
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(121 citation statements)
references
References 55 publications
3
111
4
1
Order By: Relevance
“…A recent analysis of 2031 patients, who received their first renal allograft at the Medical University of Vienna between 1990 and 2003, showed that RAS inhibitor therapy was associated with a significantly higher patient (74 versus 53%, P=0.001) and graft (59 versus 43%, P¼0.002) survival at 10 years after transplant as compared with non-RAS inhibitor therapy (Heinze et al, 2006). This is at variance with a previous systematic review of 21 studies consisting of 1549 patients on the effect of RAS inhibitor therapy after kidney transplantation that failed to show any beneficial effect on patient and graft survival over a median follow-up of 27 months (Hiremath et al, 2007).…”
Section: Proteinuriacontrasting
confidence: 54%
“…A recent analysis of 2031 patients, who received their first renal allograft at the Medical University of Vienna between 1990 and 2003, showed that RAS inhibitor therapy was associated with a significantly higher patient (74 versus 53%, P=0.001) and graft (59 versus 43%, P¼0.002) survival at 10 years after transplant as compared with non-RAS inhibitor therapy (Heinze et al, 2006). This is at variance with a previous systematic review of 21 studies consisting of 1549 patients on the effect of RAS inhibitor therapy after kidney transplantation that failed to show any beneficial effect on patient and graft survival over a median follow-up of 27 months (Hiremath et al, 2007).…”
Section: Proteinuriacontrasting
confidence: 54%
“…Clinically, patient and allograft survival improved in individuals treated with an ACE-I or ARB (229) but this was not confirmed in large registry analyses (230). In a meta-analysis of randomized controlled trials, RAS blockade lowered the GFR by about 6 mL/min and proteinuria by about 0.5 g/d over a two year time period (231). In the ''Angiotensin II Blockade in Chronic Allograft Nephropathy (ABCAN)'' trial transplant recipients were randomly assigned to receive losartan or placebo early after transplantation, continuing for 5 years (232).…”
Section: Key Molecular Effector Systems and Therapies In Renal Fibrosismentioning
confidence: 99%
“…In direct comparison with CCB, ACEinhibitors decreased eGFR, proteinuria and haemoglobin and increased potassium. ACEinhibitor and angiotensin receptor blocker (ARBs) use was associated with improvements in proteinuria but decline in eGFR and equivocal results surrounding patient and graft survival [44] . In addition, there has been a reported increased incidence of angioedema in those treated with ACEinhibitors or ARBs and mammalian target of rapamycin inhibitors (mTOR) inhibitors suggesting that this combination of treatment should be used with caution [45] .…”
Section: Hypertensionmentioning
confidence: 99%
“…Sirolimus increases levels of proteinuria compared to CNIs at 6 mo (40.8% vs 21.4%, P = 0.006) and 12 mo (37.8% vs 18.4%, P = 0.004), although the clinical relevance has yet to be established [154] . A systematic review has found that use of RAAS blockade is associated with a significant decrease in eGFR and a reduction in proteinuria (-0.47 gm/d; 95%CI: 0.86 to 0.08) [44] . However, given that there are few trials with long follow-up, the findings need to be viewed with some caution until findings from further RCTs are available.…”
Section: Proteinuriamentioning
confidence: 99%